Controlling Inflation : The Problem of Non-Indexed Debt. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
We show that the presence of nominal non-indexed government debt could give rise to more than one equilibrium inflation rate. Conditions for this to occur are discussed in terms of ad hoc and micro-founded models. Solutions to the indeterminacy problem are examined; one solution is shown to be price indexation of debt instruments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet